2019
DOI: 10.3758/s13415-019-00693-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal approach-related motivation but spared reinforcement learning in MDD: Evidence from fronto-midline Theta oscillations and frontal Alpha asymmetry

Abstract: Major depression is characterized by abnormal reward processing and reinforcement learning (RL). This impairment might stem from deficient motivation processes, in addition to reduced reward sensitivity. In this study, we recorded 64-channel EEG in a large cohort of major depressive disorder (MDD) patients and matched healthy controls (HC) while they performed a standard RL task. Participants were asked to discover, by trial and error, several hidden stimulus-response associations having different reward proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…Results showed that depressed patients were characterized by a lack of left dominance at restingstate, whereas during the task baseline and the following decision-making process they exhibited a larger right dominance compared to healthy subjects. Gheza and colleagues [60] examined frontal alpha asymmetry differences between MDD patients and healthy subjects during reward processing and reinforcement learning. Participants were presented with a probabilistic learning task where they had to learn, by trial and error, hidden stimulus-response associations.…”
Section: ) Eeg Asymmetrymentioning
confidence: 99%
“…Results showed that depressed patients were characterized by a lack of left dominance at restingstate, whereas during the task baseline and the following decision-making process they exhibited a larger right dominance compared to healthy subjects. Gheza and colleagues [60] examined frontal alpha asymmetry differences between MDD patients and healthy subjects during reward processing and reinforcement learning. Participants were presented with a probabilistic learning task where they had to learn, by trial and error, hidden stimulus-response associations.…”
Section: ) Eeg Asymmetrymentioning
confidence: 99%
“…A meta-analysis on the association of FAA with different affective states found a moderate effect size for the relationship of right-sided resting frontal asymmetry with depression (rs = .26) as well as with anxiety (rs = .25) [3]. More recent studies continue to solidify previous findings on the relationship between depression and frontal hemispheric asymmetry, showing that depressed individuals present negative FAA scores [16], indicating greater right-lateralized activity, in contrast to the balanced cortical activity shown by healthy controls [17][18][19]. Results on anxiety are scarcer and more contradictory, however.…”
Section: Introductionmentioning
confidence: 74%
“…The findings from these studies include an elevated absolute or relative alpha power at parietal, frontal, or occipital sites. Researchers have also reported the role of theta band rhythms in connection with MDD [71]. There is an increasing body of evidence indicating that the lower gamma band oscillatory power can be a prospective biomarker for MDD [72].…”
Section: Neural Oscillations As Biomarkersmentioning
confidence: 99%